Analysis of the Presentation of Financial Statements to non-Profit Oriented Organizations at the Moelyani Orphanage in Malang City - Muhammad Tulus Efendi; Dwi Anggarani; Endah Puspitosarie (Optima Science, 2024)
The conduct of this research is based on the existence of special regulations regarding financial statements presented by non-profit organizations, the emergence of this regulation is due to differences in the goals of profit-oriented organizations with nonprofit oriented organizations. Regulations for non-profit organizations, the difference between ISAK 35 and profit-oriented organizations is the presentation of reports and reports that must be presented by the organization, although there have been guidelines in the regulation and there have been examples shown, but there are still many non-profit organizations that have not implemented ISAK 35, this is evidenced by several previous studies that have negative results, or not in accordance with ISAK 35, the cause is ignorance of the organization with the existing rules, from this phenomenon, the researcher decided to raise research with the object, namely the Moelyani Orphanage located in Klojen District Malang City, from the results of the study also turned out to have results that are in line with previous studies that have been done, namely the orphanage has not implemented financial statements which are certainly not in accordance with the ISAAC.